EXHIBITION OF THE 11TH ARCHAEOLOGICAL CONGRESS IN KYIV IN 1899 IN THE CONTEXT OF THE DEVELOPMENT OF MUSEUM WORK IN UKRAINE - Кравченко, Інна (SWorldJournal, 2024)
The article is devoted to the history of the Exhibition of the 11th Archaeological Congress in Kyiv in 1899. The structure (departments) of the exhibition, the composition of the exhibits, and their geographical origin are considered. Institutions and pe